Bleach. 66, Sorry I am strong - Kubo, Tite (Shonen Jump manga., 2016)
"Ichigo Kurosaki never asked for the ability to see ghosts--he was born with the gift. When his family is attacked by a Hollow--a malevolent lost soul--Ichigo becomes a Soul Reaper, dedicating his life to protecting the innocent and helping the tortured spirits themselves find peace. Find out why Tite Kubo's Bleach has become an international manga smash-hit!"--Amazon.